Proceedings of the International Workshop on Data Science for Macro-Modeling 2014
DOI: 10.1145/2630729.2630739
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of traffic flow using passive cell-phone data

Abstract: In this paper we present preliminary results for estimating traffic flow using passive cell-phone network information. Two datasets are considered: (a) passive cell-phone data and (b) information provided by the English Highways Agency. Our proposed method identifies cell phone users that are traveling by car and using a linear regression model, estimates the flow for each of the links in which the road network is divided. Initial results indicate, that, under certain conditions, traffic flow can be effectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Of the studies not involved with either of the Orange Data for Development challenges, all studies apart from three [ 38 , 39 , 64 ] stated that the mobile phone CDRs they used in their research were anonymized. Few studies described the anonymization process as this was usually undertaken by the MNO beforehand.…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies not involved with either of the Orange Data for Development challenges, all studies apart from three [ 38 , 39 , 64 ] stated that the mobile phone CDRs they used in their research were anonymized. Few studies described the anonymization process as this was usually undertaken by the MNO beforehand.…”
Section: Resultsmentioning
confidence: 99%
“…Jiang et al reviewed methods for information extraction from triangulated CDR data, spatio-temporal analysis, and urban modeling [29]. Also, other studies reported real-time road traffic information extracted from the CDR data [30], [31], [32]. In [33], Janecek et al proposed a novel approach combining signaling data ('idle' device information) together with CDR (SigCDR) to obtain canonical information of the mobile users in an area.…”
Section: Introductionmentioning
confidence: 99%
“…The CDRs datasets overcome the acquisition problems (financially, time consuming), but their projection and trajectories tracing still time and resource consuming. The researchers try to solve this limitation by selecting the samples randomly from the CDRs, and obtain the highly frequent records [60,62,30,42,63,64,32,10,33,20,12,28].…”
Section: Introductionmentioning
confidence: 99%